The effect of enhanced glycolysis on cardiac aging - Anna Faakye; Kylene M. Harold; Satoshi Matsuzaki; Atul Pranay; Maria F. Mendez Garcia; Brooke L. Loveland; Sandra N. Rigsby; Frederick F. Peelor; Craig Eyster; Benjamin F. Miller; Timothy M. Griffin; Michael Kinter; et al. (GeroScience, 2025)
Cardiac aging is associated with metabolic changes, including an increased reliance on glycolysis, and an increased susceptibility to cardiovascular diseases. This study explores the relationship between enhanced cardiac glycolysis and aging using the Glyco Hi mouse model, characterized by constitutively elevated glycolysis. We compared cardiac function, metabolism, mitochondrial performance, and hallmarks of aging between aged (21 and 24 months) Glyco Hi and wild-type (WT) mice across sexes. Our findings reveal modest reductions in cardiac function in aged Glyco Hi mice compared to WT mice, with sex-specific differences in heart size and collagen concentration. Female Glyco Hi hearts exhibited hypertrophy without fibrosis, while males showed elevated collagen levels. Whole-body metabolic assessments revealed similar energy expenditure and respiratory patterns across genotypes, with females displaying less circadian-associated variation in metabolism. Mitochondrial analyses showed that aged Glyco Hi hearts maintained metabolic adaptations favoring glycolysis but did not exhibit significant bioenergetic dysfunction or oxidative stress. Pyruvate dehydrogenase activity, initially elevated in younger Glyco Hi hearts, normalized to WT levels with age. Proteomic and metabolomic analyses highlighted distinct profiles between genotypes, with Glyco Hi hearts exhibiting increased glycolytic enzyme levels and reduced abundance of fatty acid oxidation proteins. Despite these differences, indicators of oxidative stress, proteostasis, and cellular senescence were comparable between genotypes, suggesting no acceleration of aging-related dysfunction. This study demonstrates that increased cardiac glycolysis alone does not suffice to drive accelerated cardiac aging. Instead, metabolic and functional changes in aged Glyco Hi hearts reflect adaptations rather than pathological declines, providing insights into potential metabolic targets for interventions against cardiac aging.